Minat Mahasiswa Prodi Akuntansi untuk Mengikuti Pendidikan Profesi Akuntansi - Hari Purnama (Ideguru: Jurnal Karya Ilmiah Guru, 2022)
The purpose of this study is to find out empirically the interest of accounting study program students in following the accounting profession education which is influenced by factors of perception of the accounting profession, education costs, perception of study period, career motivation and economic motivation. This type of survey uses a questionnaire. The type of data is primary data. The population of all students of the Accounting Study Program at PGRI Yogyakarta University is 500 students. The sample of this research is part of the population of 85 respondents. The technique used is purposive sampling. The analysis tool uses multiple linear regression analysis with a significant level of 5%, with hypothesis testing t test, F test, and coefficient of determination. (R2) This study shows that the interest of accounting study program students in following accounting profession education is not significantly influenced by accounting profession perception factors. While the cost of education, perception of study period, career motivation and economic motivation have a positive and significant effect on the interest of accounting study program students in following accounting profession education.